The Development Of Hydrostatic Pressure Props As Learning Media Physics Of Senior High School - Sapriki, Huda Hinggo; Partono, Partono; Salim, M. Barkah (Universitas Muhammadiyah Metro, 2020)
AbstractThe props used by students of SMAN 4 metro are only able to show the concept of hydrostatic pressure through spray distance only. This resulted in the limited knowledge of students regarding the concept of hydrostatic pressure.. So researchers need to develop props that are able to show the concept of hydrostatic pressure to be more complex, can show the effect of depth to the amount of pressure, can show the amount of hydrostatic pressure in the same depth, and can show the effect of density to the amount of pressure. The purpose of this research are: (1) produces hydrostatic pressure props that work well, (2) produces hydrostatic pressure props that are suitable for learning media, and (3) to know about students respond of hydrostatic pressure props developed. This research is done by research and development method (R & D) using ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). The results of this research are: (1) Hydrostatic pressure props developed can work well, (2) the average of feasibility level media component and material is amount of 95.8% include of the criteria of props is very feasible to use as a media of learning., and (3) student's response to props amounted to90.96% means the props are very well received by the students. Keywords: Research and Development, Learning Media, Hydrostatic Pressure Tool